Pengaruh Gadget Terhadap Pertumbuhan Kerohanian Remaja Kristen - Fatieli Halawa (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
The background of this research is to see teenagers who always use gadgets both in study and at other times. Apart from that, the purpose of this research is to analyze the use of devices among adolescents and see the spiritual growth of adolescents. The results of this study will take teenagers longer to play with gadgets than pray and read the Bible. More teenagers before going to bed find time to turn on the device to open social media and other applications and forget to pray and on time to wake up is the first th ing teenagers do is open the device which makes them forget to pray. The use of gadgets always has an impact on the development of adolescent behavior, because gadgets have a variety of interesting and flexible features and applications so that they can add to the attractiveness of everyone, especially among teenagers. Excessive use of gadgets is more likely to have a negative impact on adolescent behavior including irritability, lazy learning, and even immoral acts. Therefore it is hoped that parents will always supervise the use of gadgets in adolescents, where adolescents must be able to operate gadgets properly and know the benefits of gadgets so that deviant behavior does not occur. The consequence of this research is that parents play a role in helping and guiding their children in dividing their time in playing gadgets and reading and investigating God's word so that the spiritual level of youth can increase. Christian Religious Teachers also have a role in directing teenagers to increase spiritual growth.